1971
DOI: 10.1063/1.1653476
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS OF Nb3Sn BY SHOCK WAVES

Abstract: The energy of a converging shock wave has been used to form the intermetallic compound Nb3Sn from its elemental powders. A reaction pattern indicative of compound formation is observed when a critical shock pressure is exceeded. The compound is obtained in a ``pressure-temperature quenched state'' and exhibits a transition temperature to superconductivity of 16.3°K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Specifically, the discovery of surface‐enhanced Raman scattering (SERS) greatly promoted the development and application of Raman spectroscopy 1–6. However, the mechanism of SERS is still a puzzle,7–15 even though there are two widely accepted mechanisms: the electromagnetic mechanism (EM) and chemical mechanism (CM). The difficulty in understanding the mechanism of SERS is that the two mechanisms are always coexistent.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the discovery of surface‐enhanced Raman scattering (SERS) greatly promoted the development and application of Raman spectroscopy 1–6. However, the mechanism of SERS is still a puzzle,7–15 even though there are two widely accepted mechanisms: the electromagnetic mechanism (EM) and chemical mechanism (CM). The difficulty in understanding the mechanism of SERS is that the two mechanisms are always coexistent.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the amount of explosive necessary to initiate the chemical reaction is related to the reaction temperature under ordinary conditions [31, 321. Also exothermic reactions are possible under shock wave conditions. Superconductive materials were synthesized by means of shock waves, such as Nb& [33] and Nb3Si [34] using stochiometric mixtures of the constituents.…”
Section: Shock Wave Synthesismentioning
confidence: 99%
“…A large number of review articles have appeared on surface enhanced Raman spectroscopy (SERS) emphasizing the valuable information that this technique is now providing. Several of these reviews have dealt with the theoretical and mechanistic advances in this field (329)(330)(331)(332)(333) and others have given an overview of the current topics of interest to which this technique is now being applied (334)(335)(336)(337)(338). Other SERS reviews have dealt with subjects such as the observation of adsorbates (339), electrochemical applications (340), and SERS scattering by metal colloids (341)(342)(343).…”
Section: Resonance-enhanced and Surface-enhanced Raman Spectroscopymentioning
confidence: 99%